IMPROVING STUDENTS’ SPEAKING AND NURTURING 4CS SKILLS THROUGH PROJECT-BASED LEARNING WITH ICT: A CONCEPTUAL FRAMEWORK - Muchamad Muchibbuddin Waly (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2024)
This conceptual framework delves into the pivotal role of project-based learning integrated with information and communication technology in improving speaking and nurturing the 4Cs skills such as critical thinking, creativity, collaboration, and communication in the English learning process. The paper highlights the significance of speaking skills in English proficiency and the challenges students encounter in developing communication and collaborative skills. It explores the potential of project-based learning with ICT to enhance students' speaking abilities and 4Cs skills. This study integrates various theories by conducting a thorough literature review on project-based learning, ICT, speaking, and the 4Cs skills. Utilizing reputable databases, the review encompasses electronic publications from 2016 to global studies conducted up to 2023. The limitations arise from database constraints and the omission of specific disciplines and focus in EFL classrooms. The conceptual framework addresses issues of motivation, fear, time constraints, and collaboration, resulting in an enriched learning environment where students not only improve their speaking skills but also develop essential 4C skills required for success in a rapidly changing global landscape. This study presents a conceptual framework that provides a comprehensive solution to the identified problems in improving students' speaking and 4C skills. The findings suggest that PjBL and ICT integration can be an effective learning model for developing speaking performance and the 4Cs skills, offering students opportunities to collaborate, communicate, and think critically and creatively.